Falak Manuscripts: Windows into the Intellectual and Cultural History of Southeast Asia - Arwin Juli Rakhmadi; Muhammad Hidayat (Universitas Islam Negeri Madura, 2025)
This study examines the development and role of falak (Islamic astronomy) manuscripts in Southeast Asia within the context of Islamic historiography and the transmission of knowledge from the Middle East. Scholars from the archipelago studied falak in the Middle East before developing it in their homeland, producing repetitive works to facilitate public understanding. However, limited documentation and a lack of in-depth research hinder a comprehensive understanding of the scholars’ roles in the history of falak. This study explored alternative sources, such as local manuscripts, travel notes, and oral traditions, using a multidisciplinary approach that includes philology, history, and the sociology of knowledge. The method used in this research is the philological method, a scholarly approach used to analyze, assess, and interpret ancient or historical texts, particularly in the context of manuscript studies. One of the research locations is the PEDIR Museum (Banda Aceh), the Manuscript Collection of Tarmidzi Abdul Hamid (Banda Aceh), and the Falak Center of Syaikh Tahir in Penang, Malaysia. The results show that falak science in Southeast Asia developed through networks of scholars connected to the Haramain and Egypt. The dissemination of falak manuscripts occurred through trade, missionary activity, and intellectual exchange, while adaptation to local culture preserved its relevance. The influence of the falak manuscripts in Southeast Asia includes strengthening religious authority, establishing local hisab-rukyat traditions, and playing a strategic role in harmonizing the Islamic calendar. This research confirms that the falak manuscripts are an intellectual heritage that reflects the synergy between science and the religious needs of Southeast Asian Muslim communities, while also serving as an important source for the study of the history of Islamic science in the region.